The State of the Art for Application of Resilience Thinking in Social-Ecological Systems (Sustainability in Debate, 2016)
Reinette Biggs, Maja Schlüter, Michael L. Schoon (editores). Principles for Building Resistance: SustainingEcosystem Services in Social-Ecological Systems. Cambridge University Press, 2015. 290 p.ISBN: 978-1-107-08265-6.